Pelatihan Pembaruan Bantuan Hidup Dasar untuk Meningkatkan Kecepatan dan Ketepatan Resusitasi - Muhammadong Muhammadong; Novita Ana Anggaraini; Sartika Lukman (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: Cardiac arrest is a life-threatening emergency that requires immediate and effective intervention. In many hospitals, the success rate of resuscitation remains low, partly due to inadequate Basic Life Support (BLS) skills among healthcare workers. Similar conditions were identified in the Emergency Department (ED) of RSUD dr. La Palaloi Maros, where several nurses had not received recent BLS refresher training, leading to decreased proficiency in cardiopulmonary resuscitation (CPR). Objective: This community service program aimed to improve nurses’ competence in performing rapid and accurate resuscitation through a structured Basic Life Support (BLS) refresh training Method: The program was conducted in November 2025 using a structured health education approach consisting of education, demonstration, hands-on practice, and simulation. Participants received updated materials based on the 2020–2022 American Heart Association (AHA) guidelines, followed by supervised CPR and AED practice using manikins. Skills were evaluated qualitatively through direct observation, focusing on compression quality, ventilation techniques, AED use, and team coordination. Result The training resulted in a significant improvement in nurses’ knowledge and practical skills. Participants were able to initiate chest compressions more quickly, perform compressions and ventilations with better accuracy, and use Automated External Defibrillators (AEDs) correctly. Team communication and coordination during cardiac arrest simulations also improved noticeably. Conclusion: BLS refresh training effectively enhanced the resuscitation abilities of ED nurses at RSUD dr. La Palaloi Maros. Regular and continuous refresher programs are recommended to maintain optimal CPR performance and ensure long-term readiness in emergency situations.